Dual hop relaying using CDMA and reconfigurable intelligent surfaces (RIS). (23rd June 2021) - Touati, Sami; Sammouda, Rachid; Alhussein, Musaed
In this paper, we suggest the use of reconfigurable intelligent surfaces (RIS) in dual hop relaying. There are two hops, the first one uses code division multiple access (CDMA) and the second one uses RIS as transmitter or reflector. We show that the incorporation of RIS allows to increase the throughput of conventional CDMA systems. The throughput of dual hop relaying using a combination of CDMA and RIS is larger than that of dual hop relaying based entirely on CDMA.